Voice Lessons : Local Government Organizations, Social Organizations, and the Quality of Local Governance - Alatas, Vivi; Pritchett, Lant; Wetterberg, Anna (World Bank, Washington, DC, 2014)
As part the Local Level Institutions study of local life in villages in rural Indonesia information was gathered on sampled household's participation in social activities. We classified the reported activities into four distinct types of social activity: sociability, networks, social organizations, and village government organizations. Respondents were also asked about questions about their village government: whether they were informed about village funds and projects, if they participated in village decisions, if they expressed voice about village problems, and if they thought the village government was responsive to local problems. Several findings emerge regarding the relationship between the social variables and the governance activities. Not surprisingly, an individual household's involvement with the village government organizations tends to increase their own reports of positive voice, participation, and information. In contrast, the data suggest a negative spillover on other households. There is a strong "chilling" effect of one household's participation in village government organizations on the voice, participation, and information of other households in the same village. The net effect of engagement in village government organizations is generally negative, while the net effect of membership in social organizations is more often associated with good governance outcomes. These findings indicate that existing social organizations have a potentially important role to play in enhancing the performance of government institutions in Indonesia and in the evolution of good governance more generally.